Citra Merek, Label Halal, dan Key Opinion Leaders pada Minat Beli Kopi “Cakra Rasa” (Institut Agama Islam Negeri Kudus, 2024)
Abstract This research aims to test and analyze the influence of brand image, halal labels, and Key Opinions Leaders (KOLs) on interest in buying